Rethinking the distinctions between old and new media: Introduction. (August 2019) - Lesage, Frederik; Natale, Simone
Recent approaches to media change have convincingly shown that distinctions between old and new media are inadequate to describe the complexity of present and past technological configurations. Yet, oldness and newness remain powerful ways to describe and understand media change and continue to direct present-day perceptions and interactions with a wide range of technologies – from vinyl records to artificial intelligence voice assistants such as Siri and Alexa. How can one refuse rigid definitions of old and new, while at the same time retaining the usefulness and pertinence of these concepts for the study and analysis of media change? This introduction to the special issue entitled 'Rethinking the Distinctions between Old and New Media' aims to answer this question by taking up the notion of biography. We argue that the recurrence of oldness and newness as categories to describe media is strictly related to the fact that interactions with media are embedded within a biographical understanding of time, which refers both to the life course of people or objects and to the narratives that are created and disseminated about them. Employing this approach entails considering the history of a medium against the history of the changing definitions that are attributed to it and, more broadly, to considering time not only as such but also against the narratives that make it thinkable and understandable.